Astragaloside IV Attenuates the Myocardial Injury Caused by Adriamycin by Inhibiting Autophagy - Li-Fei Luo; Lu-Yun Qin; Jian-Xin Wang; Peng Guan; Peng Guan; Na Wang; En-Sheng Ji (Frontiers Media S.A., 2021)
Astragaloside IV (ASIV) is the main active component of Astragalus, and can ameliorate cardiomyocyte hypertrophy, apoptosis and fibrosis. In this experiment, we studied how ASIV reduces the cardiotoxicity caused by adriamycin and protects the heart. To this end, rats were randomly divided into the control, ADR, ADR + ASIV and ASIV groups (n = 6). Echocardiography was used to observe cardiac function, HE staining was used to observe myocardial injury, TUNEL staining was used to observe myocardial cell apoptosis, and immunofluorescence and Western blotting was used to observe relevant proteins expression. Experiments have shown that adriamycin can damage heart function in rats, and increase the cell apoptosis index, autophagy level and oxidative stress level. Further results showed that ADR can inhibit the PI3K/Akt pathway. ASIV treatment can significantly improve the cardiac function of rats treated with ADR and regulate autophagy, oxidative stress and apoptosis. Our findings indicate that ASIV may reduce the heart damage caused by adriamycin by activating the PI3K/Akt pathway.